Type and Timing of Negative Life Events Are Associated with Adolescent Depression - Nishikawa, Saori; Fujisawa, Takashi X.; Kojima, Masahiko; Tomoda, Akemi (Frontiers in Psychiatry, 2018)
Previous studies have demonstrated an association between negative life events (NLEs) in childhood and resilience/posttraumatic growth (PTG) with regard to the pathogenesis of major depressive disorder. We hypothesized that the type and timing of NLEs interact to influence mental health in the general youth population. Therefore, the present study aimed to examine the effects of NLE timing and intensity on current depressive symptoms, and to determine the direct and indirect effects of NLEs/resilience on PTG and depression among non-clinical adolescents. Data were collected from 1,038 high school students across seven high schools in Fukui, Japan, during their freshman and sophomore years (648 boys and 390 girls, mean age = 15.71, SD = 0.524). Respondents completed a set of questionnaires designed to evaluate the type and timing of NLEs, depressive and traumatic symptoms, and PTG. Cluster analysis was used to divide participants into three groups based on outcomes: “cluster 1” (n=631), for whom depressive scores were significantly lower than other two sub-groups (p < 0.05, for both); “cluster 2” (n=52), for whom levels of current and past perceived stress associated with NLEs were significantly higher than those of the other two sub-groups (p < 0.05, for both); “cluster 3” (n=374), for whom perceived stress at the time of NLE was significantly higher than that of participants in the cluster 1 (p < .05) group, but not the cluster 2 group. Our findings indicated that exposure to NLEs at a younger age resulted in stronger negative outcomes, and that NLE timing and intensity were associated with PTG and current symptoms of depression. Furthermore, path analysis demonstrated that associations between perceived stress at the time of NLEs were direct and indirect predictors of current depression via PTG, and that PTSS and PTG mediate the association between NLEs/trait-resiliency and current depression. In conclusion, our findings suggest study suggests that event intensity, NLE timing, and gender might play roles inmay play a role in emotional vulnerability during adolescence.